PREVALENCE AND CLINICAL CHARACTERIZATION OF MOUTH BREATHING PATIENTS IN VIÑA DEL MAR AND QUILPUÉ, CHILE - Finger Z, Valentina; Henríquez R, Cristina; Muñoz A, Daniela; Barraza, Alan (Applied Sciences in Dentistry, 2020)
Objective: This study aimed to clinically characterize and determine the prevalence of mouth breathing in the pediatric population. Materials and methods: 383 students, aged 6 to 13 years, from public and private subsidized schools were analyzed. Clinical criteria were applied, and measurement of maximum nasal inhalation flow (PNIF) was performed to determine their breathing condition (Mouth, Nasal, or Mixed). Statistical analysis of the data was carried out through Stata SE 10.1, R-Cran 2.13.1, and Minitab 15. Results: The prevalence of mouth breathers was 18,80%, mixed breathers 17,49%, and nasal breathers 63,71%. The most common facial characteristic was the presence of eye bags (82%) and dry lips (78%). The maximum nasal inhalation flow (PNIF) average registered in mouth breathing patients was 54,4 L/min, meanwhile in nasal breathing patients was 84,7 L/min. Conclusion: Mouth-breathers are a relevant percentage of the examined population. Early intervention of pediatricians is transcendental for the diagnosis, derivation, and treatment of this syndrome in order to limit future complications.